Feasibility of Producing Acceptable Carotene and Energy Rich Taro Crisps with Deep Palm-Oil Frying in Nigeria - Ukpabi, U.J.; Chijioke, U.; Mbanaso, E.N.A. (Pakistan Journal of Nutrition, 2013)
Corms of a high yielding taro genotype (NCe006) were used to assess the feasibility of producing acceptable pro vitamin A and energy rich taro crisps after deep oil frying with crude red palm oil. Frying with refined palm oil was used as control. Results showed that the taro crisps produced with the crude palm oil had 44 μg/g carotene content while the crisps fried with refined palm oil had only 0.77 μg/g carotene content. Sensory evaluation scores by semi trained organoleptic panelists showed that the high energy (1.8 MJ/100 g) pro-vitamin A rich crisps were generally acceptable to them. The pro-vitamin A rich crisps can be used as a tool (snack food) against vitamin A deficiency (VAD) syndrome amongst children and reproductive women in Nigeria.